Compensatory Growth of the Sandbar Shark in the Western North Atlantic Including the Gulf of Mexico - Romine, J. G.; Musick, John A.; Johnson, R. A. (Marine and Coastal Fisheries, 2013)
The number of Sandbar Sharks Carcharhinus plumbeus in the western North Atlantic Ocean has experienced a drastic decline since the early 1980s, reaching a minimum during the early 1990s. Catch rates in the early 1990s were a mere 25% of those during the 1980s. According to several fishery-independent surveys, the low point in Sandbar Shark abundance followed a period of high exploitation. Growth models fit to age-length data collected from 1980 to 1983 and from 2001 to 2004 were compared to investigate potential changes in parameter estimates that might reveal compensatory responses in the Sandbar Shark population. Statistical differences were found between the model parameters for the two time periods, but the differences in growth rates were minimal. The parameters from the three-parameter von Bertalanffy growth model for female sharks during the 1980-1983 and 2000-2004 time periods were as follows: L = 188.4 and 178.3cm FL; k = 0.084 and 0.106; and t(0) = -4.097 and -3.41. For males the growth parameters were as follows: L = 164.63 and 173.66cm; k = 0.11 and 0.11; and t(0) = -3.62 and -3.33. The estimated age at 50% maturity for female Sandbar Sharks changed from 15years to 12.49years between the two time periods.